2005
DOI: 10.1113/expphysiol.2005.030189
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of estimated human muscle capillary blood flow during recovery from exercise

Abstract: The kinetic characteristics of muscle capillary blood flow (Q cap ) during recovery from exercise are controversial (e.g. one versus two phases). Furthermore, it is not clear how the overallQ cap kinetics are temporally associated with muscle oxygen uptake (V O 2 m ) kinetics. To address these issues, we examined the kinetics ofQ cap estimated from the rearrangement of the Fick equation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 56 publications
(150 reference statements)
7
57
0
Order By: Relevance
“…Nevertheless, it is important to note that our data support the notion that both INT exercise protocols display similar increased O 2 delivery conditions as has been observed within the light-intensity knee-extension exercise domain (Lutjemeier et al 2005). Moreover, Ferreira et al (2005a) showed that the drop in muscle capillary blood flow is larger upon the immediate cessation of moderate-intensity compared to light-intensity cycling and suggested that the removal of the muscle pump was responsible for this decline. In light of this, the inclusion of the moderate work rate during the recovery of INT 2 may increase the muscle pump effect and account for the decrease in DHHb/VO 2 during INT2 compared to INT1.…”
Section: Improved Blood Flow Distribution During Int 2 Versus Intsupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, it is important to note that our data support the notion that both INT exercise protocols display similar increased O 2 delivery conditions as has been observed within the light-intensity knee-extension exercise domain (Lutjemeier et al 2005). Moreover, Ferreira et al (2005a) showed that the drop in muscle capillary blood flow is larger upon the immediate cessation of moderate-intensity compared to light-intensity cycling and suggested that the removal of the muscle pump was responsible for this decline. In light of this, the inclusion of the moderate work rate during the recovery of INT 2 may increase the muscle pump effect and account for the decrease in DHHb/VO 2 during INT2 compared to INT1.…”
Section: Improved Blood Flow Distribution During Int 2 Versus Intsupporting
confidence: 84%
“…Our data suggest that the increase in power output of the recovery period of INT 2 is accompanied by greater oxidative phosphorylation contribution during the 10 s work period to meet the energy demands. The elevated VO 2 during INT2 may be associated with the speeding of VO 2 kinetics over the recovery work transition compared to INT 1, as a function of the improved blood flow distribution at the onset of the work period that has been observed elsewhere (DiMenna et al 2010;Ferreira et al 2005aFerreira et al , 2005bFerreira et al , 2006Ferreira et al , 2005cFerreira et al , 2005dHarper et al 2006;Hughson et al 1996). In particular, Grassi et al (2000) observed an *25% speeding in VO 2 kinetics at the onset of a highintensity exercise in a model in which blood flow was elevated before the onset of exercise to meet the O 2 requirements expected during an abrupt transition to highintensity exercise.…”
Section: Improved Blood Flow Distribution During Int 2 Versus Intmentioning
confidence: 95%
“…Therefore HHb kinetics are considered a more accurate marker of muscle tissue oxygenation than O 2 Hb kinetics [23,26,27]. As demonstrated by Ferreira et al [5], HHb recovery kinetics following submaximal exercise can be adequately assessed by the mean response time (i.e. time delay+time constant of mono-exponential decrease), approximating the time to reach 63 % of the response.…”
Section: Nirsmentioning
confidence: 98%
“…Whereas O 2 delivery is determined by muscle blood flow and arterial O 2 content, O 2 utilization is associated with oxidative capacity of skeletal muscles. Studies in healthy untrained individuals have provided evidence that metabolic recovery is limited by O 2 utilization, rather than O 2 delivery [5][6][7]. In CHF patients, both impairments in muscle blood flow [8,9] and muscle oxidative capacity [10,11] have been documented.…”
Section: Introductionmentioning
confidence: 97%
“…Such investigations require the ability to follow the dynamics of V O 2 and Q o 2 in separatum, the latter of which has proven more challenging. However, inferences regarding Q o 2 at the level of the microvasculature have been performed using near infrared spectroscopy in conjunction with pulmonary measures of V O 2 to approximate muscle V O 2 during the transition from rest to steady-state exercise and during ramp exercise protocols (7,8). Although each of these approaches have their own set of caveats, such techniques may prove useful in providing further insight to the centrally mediated peripheral dysfunction in CHF and other diseases.…”
mentioning
confidence: 99%